INTEGRATING FACTOR
Test for exactness and find the general solution:
1. y(x2 + y)dx + x(x2 − 2y)dy = 0
2. (2y4 + 1)dx + 4xy3dy = 0
3. y(x3y − 1)dx + x(xy4 − 1)dy = 0
4. y2dx + xydy = 0
5. y(y − 1)dx + xdy = 0
1. "y(x^2 + y)dx + x(x^2 \u2212 2y)dy = 0"
"(x^2y + y^2)dx + (x^3 \u2212 2xy)dy = 0"
"M(x,y)dx+N(x,y)dy=0"
"M(x,y)=x^2y+y^2\\implies{\\partial M(x,y)\\over \\partial y}=M_y =x^2 +2y"
"N(x,y)=x^3-2xy\\implies{\\partial N(x,y)\\over \\partial x}=N_y =3x^2 -2y"
hence not exact since "M_y \\ne N_x"
Integrating Factor = "e^{ \\int^x {M_y -N_x\\over N}dx }=e^{ \\int^x { x^2+2y-3x^2+2y\\over x^3-2xy}dx }"
="e^{ \\int^x { -2(2y-x^2)\\over x(2y-x^2)}dx}=e^{\\int -{2\\over x}dx}"
="e^{-2\\int {1\\over x}dx}=e^{lnx^{-2}}={1\\over x^2}"
multiplying the differential equation with the integrating factor "{1\\over x^2}" gives
"{1\\over x^2}[(x^2y + y^2)dx + (x^3 \u2212 2xy)dy = 0]"
"[{x^2y+y^2\\over x^2}]dx+[{x^3-2xy\\over x^2}]dy=0"
"M(x,y)=y+{y^2\\over x^2}\\implies{\\partial M(x,y)\\over \\partial y}=M_y =1+{2y\\over x^2}"
"N(x,y)=x-{2y\\over x}\\implies{\\partial N(x,y)\\over \\partial x}=N_y =1 +{2y\\over x^2}"
hence exact since "M_y = N_x=1+{2y\\over x^2}"
There exist a function "\\mu(x,y)" such that
"{\\partial \\mu(x,y)\\over \\partial x}=M(x,y)=y+{y^2\\over x^2}" and
"{\\partial \\mu(x,y)\\over \\partial y}=N(x,y)=x-{2y\\over x}"
let "\\mu(x,y)=\\int^xM(x,y)dx+g(y)"
"=\\int^x(y+{y^2\\over x^2})dx+g(y)"
"\\mu(x,y)=xy-{y^2\\over x}+g(y)"
"\\implies {\\partial \\mu(x,y)\\over \\partial y}=x-{2y\\over x}+{\\partial g(y)\\over \\partial y}"
"\\implies x-{2y\\over x}+{\\partial g(y)\\over \\partial y}=x-{2y\\over x}"
"\\implies \\int g (y)=\\int 0dy \\implies g(y)=0"
"\\implies \\mu(x,y)=xy-{y^2\\over x}+0"
"\\therefore" The general solution is thus "xy-{y^2\\over x}=c"
2. "(2y^4 + 1)dx + 4xy^3dy = 0"
"M(x,y)=2y^4+1\\implies{\\partial M(x,y)\\over \\partial y}=M_y =8y^3"
"N(x,y)=4xy^3\\implies{\\partial N(x,y)\\over \\partial x}=N_y =4y^3"
hence not exact since "M_y \\ne N_x"
Integrating Factor = "e^{ \\int^x {M_y -N_x\\over N}dx }=e^{ \\int^x { 8y^3-4y^3\\over 4xy^3}dx }=e^{ \\int^x { 1\\over x}dx }=e^{ lnx}=x"
multiplying the differential equation with the integrating factor "x" gives
"x[(2y^4 + 1)dx + 4xy^3dy = 0]"
"(2xy^4 + x)dx + 4x^2y^3dy = 0"
"M(x,y)=2xy^4+x\\implies{\\partial M(x,y)\\over \\partial y}=M_y =8xy^3"
"N(x,y)=4x^2y^3\\implies{\\partial N(x,y)\\over \\partial y}=N_y =8xy^3"
hence exact since "M_y = N_x=8xy^2"
There exist a function "\\mu(x,y)" such that
"{\\partial \\mu(x,y)\\over \\partial x}=M(x,y)=2xy^4+x" and
"{\\partial \\mu(x,y)\\over \\partial y}=N(x,y)=4x^2y^3"
let "\\mu(x,y)=\\int^yN(x,y)dy+g(x)"
"=\\int^y4x^2y^3dy+g(x)"
"\\mu(x,y)=x^2y^4+g(x)"
"\\implies {\\partial \\mu(x,y)\\over \\partial x}=2xy^4+{\\partial g(x)\\over \\partial x}"
"\\implies 2xy^4+{\\partial g(x)\\over \\partial x}=2xy^4+x"
"\\implies \\int d g (x)=\\int xdx \\implies g(x)={x^2\\over 2}"
"\\implies \\mu(x,y)=x^2y^4+{x^2\\over 2}"
"\\therefore" The general solution is thus "x^2y^4+{x^2\\over 2}=c"
3."y(x^3y \u2212 1)dx + x(xy^4 \u2212 1)dy = 0"
"(x^3y ^2\u2212 y)dx + (x^2y^4 \u2212 x)dy = 0"
"M(x,y)=x^3y ^2\u2212 y\\implies{\\partial M(x,y)\\over \\partial y}=M_y =2x^3y-1"
"N(x,y)=x^2y^4 \u2212 x\\implies{\\partial N(x,y)\\over \\partial x}=N_x =2xy^4-1"
hence not exact since "M_y \\ne N_x"
The integrating factor of the form p(x) or p(y) do not exist for the differential equation hence has no solution
4."y^2dx + xydy = 0"
"M(x,y)=y^2\\implies{\\partial M(x,y)\\over \\partial y}=M_y =2y"
"N(x,y)=xy\\implies{\\partial N(x,y)\\over \\partial x}=N_x =y"
hence not exact since "M_y \\ne N_x"
Integrating Factor = "e^{ \\int^x {M_y -N_x\\over N}dx }=e^{ \\int^x { 2y-y\\over xy}dx }=e^{ \\int^x { 1\\over x}dx }=e^{ lnx}=x"
multiplying the differential equation with the integrating factor "x" gives
"x[ y^2dx + xydy = 0]"
"xy^2dx + x^2ydy = 0"
"M(x,y)=xy^2\\implies{\\partial M(x,y)\\over \\partial y}=M_y =2xy"
"N(x,y)=x^2y\\implies{\\partial N(x,y)\\over \\partial x}=N_x =2xy"
hence exact since "M_y = N_x=2xy"
There exist a function "\\mu(x,y)" such that
"{\\partial \\mu(x,y)\\over \\partial x}=M(x,y)=xy^2" and
"{\\partial \\mu(x,y)\\over \\partial y}=N(x,y)=x^2y"
let "\\mu(x,y)=\\int^xM(x,y)dx+g(y)"
"=\\int^xxy^2dy+g(x)"
"\\mu(x,y)={x^2\\over 2}y^2+g(x)"
"\\implies {\\partial \\mu(x,y)\\over \\partial y}=x^2y+{\\partial g(y)\\over \\partial y}"
"\\implies x^2y+{\\partial g(y)\\over \\partial y}=x^2y"
"\\implies \\int d g (y)=\\int 0dx \\implies g(x)=0"
"\\implies \\mu(x,y)={1\\over 2}x^2y^2+0"
"\\therefore" The general solution is thus "{1\\over 2}x^2y^2=c"
5. "y(y \u2212 1)dx + xdy = 0"
"(y^2 \u2212 y)dx + xdy = 0"
"M(x,y)=y^2-y\\implies{\\partial M(x,y)\\over \\partial y}=M_y =2y-1"
"N(x,y)=x\\implies{\\partial N(x,y)\\over \\partial x}=N_x =1"
hence not exact since "M_y \\ne N_x"
Integrating Factor = "e^{ \\int^y {M_y -N_x\\over N}dy }=e^{ \\int^y { 1-2y+1\\over y^2-y}dy }=e^{ \\int^y{ 2-2y\\over y^2-y}dy }"
evaluate "{ \\int^y{ 2-2y\\over y^2-y}dy }" by partial fraction
"{ 2-2y\\over y(y-1)}={A\\over y}+{B\\over y-1}"
"{ 2-2y\\over y(y-1)}={A(y-1)+By\\over y(y-1)}"
"\\implies 2-2y=Ay-A+By=(A+B)y-A"
equating coefficients of y terms together and constants together we have
"A+B=-2 and A=-2\\implies B=0"
"\\therefore{ 2-2y\\over y(y-1)}={-2\\over y}+{0\\over y-1}={-2\\over y}"
"\\therefore { \\int^y{ 2-2y\\over y^2-y}dy }=-2\\int{1\\over y}dy=-2lny=ln y^{-2}"
"\\therefore" Integrating Factor "=e^{lny^{-2}}={1\\over y^2}"
multiplying the differential equation with the integrating factor "{1\\over y^2}" gives
"{1\\over y^2}[ (y^2 \u2212 y)dx + xdy = 0]"
"{y-1\\over y}dx + {x\\over y^2}dy = 0"
"M(x,y)={y-1\\over y}\\implies{\\partial M(x,y)\\over \\partial y}=M_y ={1\\over y^2}"
"N(x,y)={x\\over y^2}\\implies{\\partial N(x,y)\\over \\partial x}=N_x ={1\\over y^2}"
hence exact since "M_y = N_x={1\\over y^2}"
There exist a function "\\mu(x,y)" such that
"{\\partial \\mu(x,y)\\over \\partial x}=M(x,y)={y-1\\over y}" and
"{\\partial \\mu(x,y)\\over \\partial y}=N(x,y)={x\\over y^2}"
let "\\mu(x,y)=\\int^xM(x,y)dx+g(y)"
"=\\int^x{y-1\\over y}dx+g(y)"
"\\mu(x,y)=x{y-1\\over y}+g(y)"
"\\implies {\\partial \\mu(x,y)\\over \\partial y}={x\\over y^2}+{\\partial g(y)\\over \\partial y}"
"\\implies {x\\over y^2}+{\\partial g(y)\\over \\partial y}={x\\over y^2}"
"\\implies \\int d g (y)=\\int 0dy \\implies g(y)=0"
"\\implies \\mu(x,y)=x{y-1\\over y}+0"
"\\therefore" The general solution is thus "x{y-1\\over y}=c"
Comments
Leave a comment